Procedimentos de ensino e de testes de construção e leitura de sentenças com compreensão - SAMPAIO, Maria Elizângela Carvalho (Universidade Federal do Pará, 2011)
The analysis on ordinal relations in which the responding is under control of relational properties such as first, second, third and so on, based on the equivalence paradigm, constitutes an important way to comprehend verbal behavior (syntax). Five studies aimed to evaluate the emergency of new sentences with three or four words(articles, nouns, adjectives or verbs and adverbs), based on the positions taken by them in each sentence taught independently. Five pre-school children participated on the Study 1, envolving three words. All the participants were given matching-to-sample training procedures, equivalence tests, training through response chaining, sequences production training, conectivity and reading and comprehension tests. On Study 2, other five children from middle-school were given the same training procedures and tests, with four words. On Study 3, four children were submitted to the procedure by chaining, sequence production tests, conectivity and reading with comprehension using four words. On Study 4, other four children with school failure history were given the same tests and teaching procedures of Studies 1 and 2, with four words. On Study 5, three other children also with school failure history were given the same procedure adopted on Study 3, with four words. Participants didnt have fluent phrase reading, but readed words separately. Experimental sessions occured in a room of the School. A microcomputer was used in the study as well as a specific software to control the stimulus presentation and record the behavioral data. Three sets of stimuli were used: A (drawins), B (upper case words) and C (lower case words), to teach AB and AC conditional relations and BC/CB tests. On training by chaining, three different sentences were used. On first trial, the word UM, for example, was presented on the choice area. A touch on the word produced as a consequence its displacement to the construction area on the upper part of the screen, a graphic animation was presented with a sound muito bem (very good), legal (cool), certo (right). Following, two words were presented simultaneously on the screen and the participants should touch one of them and then the other one. In case the words were put in the correct 12 order, the same previous consequence were presented and the same set of words were presented again in different positions on the choice area.In case of an answer different from the programed by the experimenter, a blackout of the screen was produced for 3s and a new set of words were presented, side-by-side on the choice area. After teaching the baseline, sequences production and conectivity tests were applied to verify the emergence of six new sentences (except Study 1), based on previously taught words recombination. Finally, a reading comprehension test with new phrases were presented the participants. For example, on the presence of a picture, three different sentences on capital letters were presented and the participant should choose which was the correct sentence. In all the studies, the participants reached the rightness criteria, three consecutive times, without no mistake, though some of them have needed re-exposure. On Studies 1 and 2, all participants responded consistently to the tests and read the new sentences fluently and with comprehension. On Study 3, a participant built the six new sentences readily. None read with comprehension the reading tests. On Study 4, three participants built the new sentences readily and a participant didnt respond to the conectivity test. Two participants responded to the reading with comprehension tests. On Study 5, two participants built four new sentences readily. On Studies 3 and 5, participants didnt respond to the reading with comprehension tests. These results demonstrated the emergency of new sentences, without any aditional train, based on the teaching with three independent sentences. The results of the reading with comprehension tests shown a coherence with the equivalence paradigm. Its concluded that stimuli used were functionally equivalents and exerted ordinal functions by the position that each one took place on the sentences.